ANALYSIS OF PRODUCTIVE WAQF PRACTICE AND MANAGEMENT: USING SWOT ANALYSIS METHOD - Permaisela, Dera (al-Uqud : Journal of Islamic Economics, 2019)
This study aims to determine the practice of waqf, productive waqf management of sengon Plantations until the time of harvest and development of productive waqf in Sengon plantation. This study uses qualitative methods, then the results of the analysis using SWOT analysis. The results of this study indicate that the fund of productive waqf assets will be received in 2020 and fully submitted to the Republika Dompet Dhuafa. In the SWOT analysis, the strength are the land is fertile, the ability of Dompet Dhuafa management to appoint farmer is good, and as nazhir Dompet Dhuafa has an excessive experiences in productive waqf management. The weaknesses are the planting space is too close and the lack of spraying of pests in the sengon tree. The opportunities are the opening of cooperation with timber companies / traders, the opening of export opportunities to increase government foreign exchange and the good market price of sengon trees. While the threat faced is the presence of natural factors such as bad weather which causes the sengon tree to collapse.